PIF transcription factors-versatile plant epigenome landscapers - Ammari, Moonia; Maseh, Kashif; Zander, Mark (Frontiers in Epigenetics and Epigenomics, 2024)
Plants are exquisitely responsive to their local light and temperature environment utilizing these environmental cues to modulate their developmental pathways and adjust growth patterns. This responsiveness is primarily achieved by the intricate interplay between the photoreceptor phyB (phytochrome B) and PIF (PHYTOCHROME INTERACTING FACTORs) transcription factors (TFs), forming a pivotal signaling nexus. phyB and PIFs co-associate in photobodies (PBs) and depending on environmental conditions, PIFs can dissociate from PBs to orchestrate gene expression. Until recently, the mechanisms governing epigenome modifications subsequent to PIF binding to target genes remained elusive. This mini review sheds light on the emerging role of PIFs in mediating epigenome reprogramming by recruiting chromatin regulators (CRs). The formation of numerous different PIF-CR complexes enables precise temporal and spatial control over the gene regulatory networks (GRNs) governing plant-environment interactions. We refer to PIFs as epigenome landscapers, as while they do not directly reprogram the epigenome, they act as critical sequencespecific recruitment platforms for CRs. Intriguingly, in the absence of PIFs, the efficacy of epigenome reprogramming is largely compromised in light and temperature-controlled processes. We have thoroughly examined the composition and function of known PIF-CR complexes and will explore also unanswered questions regarding the precise of locations PIF-mediated epigenome reprogramming within genes, nuclei, and plants.